Biological Functions and Health Benefits of Flavonoids in Fruits and Vegetables: A Contemporary Review - Xiaoyuan Zheng; Xuejiao Zhang; Fankui Zeng (Foods)
Flavonoids, being prevalent in fruits and vegetables, are essential to the diverse stages of plant growth, development, and storage. Furthermore, flavonoids have been shown to exert substantial beneficial effects on human health, prompting heightened scientific interest in their potential advantages. This review elucidates the functions of flavonoids in fruits and vegetables, confirming their position as natural sources of these compounds, despite the differences in type and concentration among various species. This review elucidates the significance of flavonoids in the growth and development of fruits and vegetables, highlighting their roles in enhancing pigmentation and providing protection against both biotic and abiotic stresses. In relation to human health, flavonoids are recognized for their ability to combat aging, mitigate inflammation, safeguard the nervous system, and promote overall well-being. Additionally, this review proposes avenues for future research in the domain of flavonoids, underscoring the necessity for ongoing exploration of their potential applications and benefits.